The Church in the constitution of an urban network in the eighteenth century in Brazil - Andrade, Adriano Bittencourt (2022)
The understanding of the complex and asymmetric power relations between the agents that produce the space allows us to identify internationalities and distance ourselves from a naturalized perspective of the dynamics of occupation and use of territories. In this article, based on this fundamental premise to the studies of Historical Geography, the objective is to analyze the role of the Church as hegemonic agent in the relations of production of space in colonial Brazil. From the empirical of the 18th century in the Recôncavo Baiano (around Salvador, colonial capital until 1763), in the light of primary research in Brazilian and Portuguese archives, seven imbricated roles assumed by the Church (Regular, Secular and Lay Orders) in the constitution and dynamics of that regional network that articulated the city and inland villages are related. As a result, it is presented a cartogram that overlays the units built by the Church (matrices and chapels), the nuclei of settlement and the roads (terrestrial and fluvio maritime) that crossed the region.